The potential of SWCNTs to extend the IR-absorption of silicon solar cells. (30th October 2021) - Wieland, L.; Rust, C.; Li, H.; Jakoby, M.; Howard, I.; Li, F.; Shi, J.; Chen, J.; Flavel, B.S.
Abstract: Single wall carbon nanotubes (SWCNTs) have long been proposed as a candidate to enhance existing photovoltaic materials by providing an extension to the light absorbed in the infrared. In this work, we discuss the validity of this statement for silicon solar cells and couple a bifacial silicon solar cell to an organic SWCNT cell in a 4-terminal stack. Single chiral species of (6, 5), (7, 6), and (10, 3) are used in the organic cell and the overall contribution to photocurrent from the SWCNTs is discussed in terms of the diameter dependent quantum efficiency, film thickness, the transmittance of silicon, the spectral overlap of the SWCNT's absorbance with the solar irradiance spectrum and the maximum obtainable current density in the infrared. Graphical abstract: The possibility of using the chirality dependent optical properties of single wall carbon nanotubes to extend the light absorption of silicon into the infrared is investigated. A bifacial silicon solar cell is combined with an organic SWCNT cell and the potential increase in photocurrent is discussed considering the material constraints of both devices. Image 1